Urban Communities in the Coastal Zone: An AHP (Analytic Hierarchy Process) Multicriteria Methodolog for the construction of a Social Vulnerability Index due the Maritime Action - Craveiro, J.; Freire, P.; Oliveira, F.; Duarte de Almeida, I.; Sancho, F. (Proceedings of the 2nd Ibero-American Congress of Social Responsibility, 2012)
This article summarizes an application of the AHP (Analytic Hierarchy Process) as a multcriteria methodology for ranking and weighting diverse collected information. The goal of this work is to build a social vulnerability index for coastal erosion. The AHP is a methodology developed in the 70s of the last century by Thomas Saaty for decision-making processes on business and economic policy options, and it has been specially adapted for different purposes, such as the consideration of environmental risk factors and prioritization of socially vulnerable elements and territorial susceptibility. This article uses an adaptation of the methodology and discusses its application in the development of studies about coastal sustainability and coastal erosion.